Exploring The Pseudo-Transformational Leadership Style That Causes The Decline of Companies in Indonesia - Prayitno Prayitno; Amron Amron; Sih Darmi Astuti (Journal of International Conference Proceedings, 2025)
Companies in Indonesia experience high pressure from the government and society who at all times use strict control over organizers. The government uses control tools in the form of supervision with its regulations, while the public uses social media to monitor the behavior of company administrators, both state-owned and private-owned enterprises in Indonesia. This research focuses on the pseudo-transformational leadership style, which they (organizers) claim to be transformational, the difference in claims between the organizers and the government and society is proven by the final results received by the organizers as a result of their actions towards individuals and companies. Research approach/design and methods: An exploratory sequential method research design was used in this research. Qualitative research, data from BUMN annual reports and unstructured interviews with 6 human resource (HR) managers selected purposively. Main findings: This study reveals that the setbacks experienced by state-owned and private enterprises are caused by unethical behavior of leaders, despotic leaders, leaders who are explorative towards employees, greedy nature, acting on personal goals and high moral abandonment